2020
DOI: 10.9734/arrb/2020/v35i130180
|View full text |Cite
|
Sign up to set email alerts
|

Review: Rice Blast Disease

Abstract: Rice blast caused by Magnaporthe grisea is the major damaging disease in nearly all rice growing nations. Economically relevance with 60 percent of total population of world depending on rice as the main source of calories, may have destructive effects of the disease, however, this pathogen has developed into a pioneering model system for researching host-pathogen interactions. The disease outbreak depends on the weather and climatic conditions of the various regions. The disease's occurrence and symptoms vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 34 publications
1
43
0
1
Order By: Relevance
“…Comparable to a study reported by Asfaha, Selvaraj, and Woldeab (2015), at higher altitude blast incidence and severity were lower probably due to low relative humidity that hinders the development of the disease, while at a lower altitude, the temperatures were high and therefore not favorable for spore germination. Reports have also shown that the incidence of rice blast is positively correlated with rainfall and relative humidity, but negatively correlated with temperature (Shahriar, Imtiaz, Hossain, Husna, & Eaty, 2020;Shafaullah, M. A. Khan, N. A. Khan, & Ysir, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable to a study reported by Asfaha, Selvaraj, and Woldeab (2015), at higher altitude blast incidence and severity were lower probably due to low relative humidity that hinders the development of the disease, while at a lower altitude, the temperatures were high and therefore not favorable for spore germination. Reports have also shown that the incidence of rice blast is positively correlated with rainfall and relative humidity, but negatively correlated with temperature (Shahriar, Imtiaz, Hossain, Husna, & Eaty, 2020;Shafaullah, M. A. Khan, N. A. Khan, & Ysir, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The disease spreads frequently under moist conditions with relative humidity ranging from 80%-100% and temperatures ranging from 25 to 30°C (Talbot 2003). Significant harvest losses have been reported in many rice-growing countries of the South-east Asia (China, Sri Lanka, Indonesia, Bangladesh, India) (Wilson and Talbot 2009;Suprapta and Khalimi 2012;Kumar and Kalita 2017) and also in other regions like South America, Australia, Korea and Philippines (Greer and Webster 2001;Pena et al 2007;Shahriar et al 2020) (Figure 1). In an outbreak of rice blast disease in Malaysia, yield loss caused by panicle blast was as high as 50-70% (Ashkani et al 2015;Zakaria and Misman 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rice blast, caused by Magnaporthe oryzae , is arguably the most destructive fungal disease of rice [ 2 ]. M. oryzae infects plants at almost all growth stages and reduces rice yield by 10–35% [ 3 ]. It is estimated that the amount of rice destroyed by rice blast disease each year is enough to feed 60 million people [ 4 ].…”
Section: Introductionmentioning
confidence: 99%